Classification, Functions, And Symbolic Meanings Of Traditional Khorezm Clothing In The Collections Of The Ichan Kala Museum-Reserve (Eurasian Journal of History, Geography and Economics, 2026)
This article presents an ethnographic analysis of traditional Khorezm clothing preserved in the collections of the Ichon-Qal’a State Museum-Reserve. The study examines the structural features of clothing, its social and functional roles, and symbolic meanings. The analysis reveals how clothing reflects age, gender, social status, and ceremonial practices in Khorezm society. The relevance of the study lies in the importance of preserving traditional cultural heritage and the scientific analysis of museum collections. The findings have both scientific and practical significance for Khorezm ethnography, museology, and the study of the history of national costume.